The Impact of Extracorporeal Shock Wave Therapy on Pain and Range of Motion in the Knee Joint - Dong Haisheng (Ilmu Inovasi Nusantara, 2024)
Knee joint sports injuries significantly affect athletes’ performance and well-being. These injuries predominantly involve damage to structures such as medial and lateral collateral ligaments, the cruciate ligaments, and menisci, alongside potential traumatic synovitis. Traditional treatments often require long recovery periods and invasive procedures which may not be feasible for all patients. This study explores the application of extracorporeal shock wave therapy (ESWT) as a non-invasive alternative. Extracorporeal shock wave therapy utilizes sound waves with mechanical properties to generate energy through the rapid compression of a medium caused by high-speed motion and vibration. This technique has been recognized for its safety, efficacy, and non-invasive nature, making it an appealing option for treating musculoskeletal disorders. ESWT focuses energy on the injured area to promote regeneration and repair processes, potentially reducing pain and enhancing recovery speed. Despite the growing global use of ESWT in orthopedics, there remains a lack of comprehensive studies specifically examining its effects on sports-related soft tissue injuries in the knee ligaments in China. This research aims to fill that gap by systematically evaluating the efficacy of ESWT in the treatment of knee ligament injuries among athletes. The study measures outcomes based on pain reduction, improvement in joint function, and overall recovery time. The innovative approach taken by using ESWT, and the significance of filling a research gap in the Chinese context. The findings are expected to contribute valuable insights into alternative treatment modalities for sports-related knee injuries, offering benefits such as reduced recovery times and avoidance of surgical interventions